Effects of Kinesio® tape vs rigid tape on shoulder muscle strength in healthy tennis players - Tanoori, P.; Nahar, A. M.; Razif, M. A. M. (International Journal of Applied Exercise Physiology, 2016)
Background: Many athletic trainers and therapists use taping to improve the performance of their athletes however, there is limited research on how and which taping techniques influence the athletesâ€™ performance. Objective: The purpose of this study was to determine the effects of applying Kinesio® tape (KT) and rigid tape on shoulder isokinetic muscle strength of healthy tennis players. Methods: Forty five male tennis players (age: 24 ± 6, weight: 75.38 ± 11.43kg, height: 177.05 ± 7.19cm) were recruited. Shoulder isokinetic muscle strength was measured with an isokinetic dynamometer before and 30 minutes after taping in three groups: with KT, with rigid tape and no tape. Results: The results revealed that the mean peak torque in KT group was significantly higher than rigid tape and control group except external rotation at 60°/s. Power with KT was significantly higher than rigid tape and control tape for all conditions but there was no significant difference between the rigid and control group (P<0.05). Conclusions: The results imply that for increasing the isokinetic muscle strength in athletes and as a result enhancing the athletic performance, facilitatory Kinesio taping is a more effective option rather than rigid taping.